2019
DOI: 10.1371/journal.pone.0210348
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of deformities and variation in shape of mentum and wing of Chironomus columbiensis (Diptera, Chironomidae) as tools to assess aquatic contamination

Abstract: Constantly, aquatic ecosystems are under pressure by complex mixtures of contaminants whose effects are not always easy to evaluate. Due to this, organisms are sought in which early warning signs may be detected upon the presence of potentially toxic xenobiotic substances. Thereby, the study evaluated the incidence of deformities and other morphometric variations in the mentum and wing of Chironomus columbiensis exposed to water from some of the Colombian Andes affected by mining, agriculture, and cattle raisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 56 publications
(95 reference statements)
0
4
0
1
Order By: Relevance
“…The 10 individuals of C. columbiensis used in this study were obtained from a colony maintained at the Laboratory of Zoology of the Universidad de Caldas (Manizales, Caldas, Colombia), confirmed by Trivinho‐Strixino (Universidade Federal de São Carlos‐Brazil‐Departamento de Hidrobiologia), under controlled temperature (22 ± 2°C), humidity (65 ± 10%), and photoperiod (12 hr light/12 hr darkness), semi‐soft reconstituted water, constant aeration, and TetraMin® crushed food (Montaño‐Campaz et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 10 individuals of C. columbiensis used in this study were obtained from a colony maintained at the Laboratory of Zoology of the Universidad de Caldas (Manizales, Caldas, Colombia), confirmed by Trivinho‐Strixino (Universidade Federal de São Carlos‐Brazil‐Departamento de Hidrobiologia), under controlled temperature (22 ± 2°C), humidity (65 ± 10%), and photoperiod (12 hr light/12 hr darkness), semi‐soft reconstituted water, constant aeration, and TetraMin® crushed food (Montaño‐Campaz et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…C. columbiensis was first described in Cali‐Colombia by Wülker, Sublette, Morath, and Martin (). Larvae of C. columbiensis have been used in environmental quality assessment in Colombia (Montaño‐Campaz, Gomes‐Dias, Restrepo, & García‐Merchán, ). In particular, Montaño () showed that C. columbiensis is more sensitive to heavy metals compared to other chironomid species broadly used ecotoxicology, such as Chironomus calligraphus , Chironomus tentans, and Chironomus riparius .…”
Section: Introductionmentioning
confidence: 99%
“…Chironomus columbiensis is one of the few species of this group identified in Colombia, described by Wülker et al (1989) and has been reported in Colombia, Brazil, Guatemala and the United States (ZipcodeZoo 2015), but its biology and ecology are still little known (Montaño-Campaz et al 2019, Ospina-Pérez et al 2019. Therefore, the objective of this study was to know the effects of temperature, availability food and type of water in the laboratory rearing of the species Chironomus columbiensis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pattern of distribution of chironomids can also serve as an indicator of the urban pollution of stream systems, molecular alterations can be complementary to conventional assessment approaches, in which genetic biomarkers were proposed as early indicators of chemical toxicity. Therefore, some species have been used as target organisms for the assessment of aquatic toxicology, especially Chironomus species, due to their high degree of sensitivity (Martínez‐Paz, 2018; Montaño‐Campaz et al, 2019). However, only a handful of genes (cytochrome P450, hormonal receptors, small heat shock proteins, and α‐enolase) have been demonstrated to be correlated with the tolerance/resistance to insecticides or heavy metals in chironomids (Martín‐Folgar & Martínez‐Guitarte, 2019; Nair et al, 2013; Planelló et al, 2010; Zheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%